The Conceptualization in the Visual Arts: Another Epistemological Domain - Vilchis Esquivel, Luz del Carmen (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2014)
The visual arts, marginalized from other knowledge areas, because of epistemological fragmentation brought by positivism and the desire to respond to the complex rapid development of new technologies, have lost the most important tasks: reflection. Speculation about the artistic action and delivery of critical judgments about their demonstrations involves introspection and think about their processes and development parameters. Imagine and create in the visual arts have become spontaneous reactions resulting from the moment intuition, forgetting important stages of concentration, abstraction, speculation and transformation of aesthetic experience. Today the arts are provoking a chain of physical reactions. Disgust, surprise, rejection, etc., of the form transgressions and not from the substance, there is an abysm between thought and reason. There is a neglect of the contents by those who fought Klee, Kandinsky, Arnheim and Gombrich and made understandable Cézanne, Duchamp and Beuys artwork. This is a reflection about the importance of epistemological domain in the visual arts, a call to return to its conceptualization and rebuild the philosophy and theory of visual arts of our time. These disciplines have a reference to the concepts that underpin theoretical aspect, a media concerning the technical aspect by which the work or artistic action is done and a poetic aspect that establishes a link between the person who creates the artwork and those who perceive and contemplate it, making a link among themselves and between them and the artwork. This requires to recognize the knowledge needs and understand both the surplus of meaning in visual arts such as socialization cultural values, both are essential structures and theoretical conceptions because from the same object or action different equally valid interpretations are given, as long as they are cognitively supported. The visual arts are a unit of knowledge, a set of knowledge unified thanks to certain principles, but not a body closed; contrary truths are in constant and dynamic relationship with other cognitive areas, affecting some people and being influenced by other. The conceptualization of the visual arts is valuable because it has a direct impact on the way of thinking, in behavior, actions and decisions of human beings, by virtue of which are seen as generators of values and cultural property.